Effect of New Peripudendal Block (PPB) in the Second Stage of Labour on Perineal Relaxation and on the Reduction of Episiotomy Rate: A Randomized Control Trial - Artur Beke (Obstetrics and Gynecology International)
Background and Objectives. We developed a new procedure peripudendal block (PPB) by modifying the traditional pudendal nerve block (PNB). Methods. In a prospective randomized study, we examined the extent to which the PPB we developed changed the rate of episiotomies, injury rates. Results. A total of 333 primiparas and 324 multiparas were included in the study. In the case of primiparas, we used the PPD procedure in 133 cases, while in the case of multiparas, we used it in 103 cases. The rate of episiotomy in primiparas was 89/133 (66.9%) with PPD and 181/200 (90.5%) without PPD p<0.02. In multiparas, the episiotomy rate was 30/103 (29.1%) with PPD and 140/221 (63.3%) without PPD p<0.02. In the case of primiparas, the rate of perineal injury and lesion was 33/133 (24.8%) with PPD, while without PPD it was 12/200 (6.0%). Examining the need for all surgical care (due to episiotomy and/or injury), a total of 103/133 cases of operative surgery were required with PPD (77/4%) while 183/200 cases were required without PPD (91.5%)p<0.02. In the case of multiparas, the rate of perineal injury and lesion was 11/103 (10.7%) with PPD, while without PPD it was 9/221 (4.1%). In the case of multiparas, a total of 41/103 cases required surgical care with PPD (39.8%), while without PPD, 147/221 cases required surgical care (66.5%)p<0.02. Conclusion. The PPB is simpler, requires less medication, can be easily mastered, and perineal relaxation can also be observed, reducing the need for an episiotomy.